PENELITIAN PENANGANAN ANAK JALANAN MELALUI RUMAH SINGGAH - Suradi Suradi (Politeknik Kesejahteraan Sosial, 2003)
Studies on the Coping of Street Children through Home Shelter.One among model which developed by the Ministry of Social Affairs in serving street children is